Higher Education – Importance and Funding in Slovenia - Maja Klun; Marina Šućur (Central European Public Administration Review)
Funding of education is becoming a particularly problematic issue, because public funding is no longer sufficient. The article considers the problems of funding higher education from the point of view of the sufficiency of funds and from the point of view of the importance of education. It illustrates methods of direct and indirect funding of education in Slovenia and presents the results of a survey in which students gave their opinions on the importance of education and on education funding. A large majority of respondents agree that the introduction of tuition fees would cause a reduction in participation in higher education and a consequent reduction in equal opportunities for education. Despite this, the largest share of respondents did not agree with the statement that in case of the introduction of tuition fees they would not enrol in education.